Clostridium difficile: Investigating Transmission Patterns Between Symptomatic and Asymptomatic Patients Using Whole Genome Sequencing. (4th October 2017) - Kong, Ling Yuan; Eyre, David; Corbeil, Jacques; Raymond, Frederic; Walker, A Sarah; Wilcox, Mark; Bourgault, Anne-Marie; Dascal, Andre; Michaud, Sophie; Toye, Baldwin; Loo, Vivian; ,
Abstract: Background: Patients with symptomatic Clostridium difficile infection (CDI) are thought to be responsible for most transmission events, but whole genome sequencing (WGS) studies have raised interest in asymptomatic carriers' role in transmission. Methods: Patients with CDI and colonization were identified using weekly screening in a study conducted during 2006–2007 at six Canadian hospitals. Isolates were typed using pulsed-field gel electrophoresis (PFGE), multi-locus sequence typing (MLST), and WGS. Toxigenic status was determined using cytotoxin testing and tcdB PCR. Incident CDI cases, not included in the initial study, were also sequenced where possible. Ward movement and typing data were combined to identify plausible donors for each CDI case, as defined by shared time and space on the same ward within predefined limits (infectious period <8 weeks and incubation period <12 weeks), or a shared ward after diagnosis of the donor within 26 weeks of the donor's discharge. Proportions of plausible donors for CDI cases that were colonized, infected, or both were examined. Results: A total of 554 samples were sequenced successfully, 348 from colonized, 201 from infected, and 5 from patients with unknown status. The NAP1/027/ST1 strain was most common among infected and colonized patients. Colonized patients predominantly carried toxigenic strains. Comparing samples from infected patients with all prior samples, a donor with a plausible ward link was found for 115 (57.2%) cases using PFGE, 127 (63.2%) using MLST, and 81 (40.3%) using WGS with a threshold of ≤2 single-nucleotide variants to determine relatedness. Examining data from the two hospitals with most complete data, across all typing methods, more cases could be linked to infected patients rather than to colonized patients. Using WGS, 26 (21.9%) cases were genetically linked to infected patients only, whereas 4 (3.4%) to colonized patients only, and 30 (25.2%) to both. Of those with a genetic link to an infected patient, 21 (17.7%) had a ward link, whereas this was found for only 1 (0.8%) case linked to a colonized patient. Conclusion: Asymptomatic carriers contribute to transmission, but CDI cases are more likely linked to other infected patients than colonized patients in this cohort with high rates of NAP1/027/ST1 strain. Disclosures: M. Wilcox, Merck & Co., Inc.: Consultant, Consulting fee. Cubist: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Grant recipient and Speaker honorarium. Alere, Actelion Pharma, Astellas, Optimer, Sanofi pasteur, Summit Pharma, bioMerieux, Da Volterra, Qiagen, Cerexa, Abbott, AstraZeneca, Pfizer, Durata Therapeutics, Seres Therapeutics, Valneva, Nabriva Therapeutics, Roche, The Medicines Company, Basilea P: Consultant, Consulting fee. Alere, Actelion Pharmaceuticals, Pharmaceuticals, Astellas, Optimer Pharmaceuticals, Sanofi pasteur, Summit Pharmaceuticals, bioMerieux, Da Volterra, Qiagen, Cerexa, and Abbott: Grant Investigator, Grant recipient.